Beyond the Clock: Revisiting Occupational Exposure Limits (OELs) for unusual work schedules in the South African Mining Industry - Engelbrecht, Ilzé; Horn, Suranie; Badenhorst, Cas J.; du Plessis, Johan L. (Safety science, 2024)
•Workers are exposed to airborne contaminants during their shifts.•OELs have been developed to protect worker health.•Standard OELs are based on exposure during conventional shifts.•OELs must be adjusted to ensure that workers with unusual shifts are protected.•OELs in the SAMI should be adjusted using the OSHA or Québec models. Workers are exposed to various stressors in their workplace and in many industries, exposure is prolonged due to unusual work schedules. Unfortunately, current Occupational Exposure Limits (OELs) are derived from calculations based on a conventional work schedule of five consecutive, eight-hour days (40 h per week) and do not compensate for prolonged exposure and shortened recovery time. Therefore, standard OELs must be adjusted to ensure worker protection. The aim of this paper was to review different mathematical models available in the literature to adjust OELs for unusual work schedules. Based on the advantages, disadvantages and practical feasibility of the different models, the Brief and Scala, Occupational Safety and Health Administration (OSHA) and Québec models were selected to calculate reduction factors (RFs, i.e., adjustment factors) for three unusual work schedules encountered in the South African Mining Industry (SAMI). Subsequently, the calculated RFs were used to establish adjusted OELs (OELA) for 15 chemical substances of interest. The Brief and Scala model yielded the most conservative RFs for all work schedule examples. However, this model may overestimate the degree to which the OELs should be lowered. The OSHA and Québec models incorporate pharmacokinetic parameters (i.e., primary health effects) and generated more realistic RFs compared to the Brief and Scala model. Although pharmacokinetic-based models are more accurate from a toxicological viewpoint, the anatomical, physiological, biochemical, and physiochemical parameters required to apply these models are not available for many chemical substances and therefore the use of such pharmacokinetic-based models is not practically feasible in South Africa. Based on the findings of this study, the authors recommend using the OSHA or Québec models for OEL adjustments in the SAMI. OELs adjusted in this manner will provide an equivalent degree of worker protection during unusual work schedules compared to conventional work shifts.